Perencanaan Jalan Setapak Pemedek dan Fasilitas Umum (FASUM) di Pura Pajinengan Gunung Tapsai Kabupaten Karangasem, Bali - A.A Gede Sumanjaya; A.A Rai Asmani K; Ida Ayu Cri Vinantya L (Universitas Warmadewa, 2021)
Karangasem Regency is one of 8 regencies in Bali Province which is located in the eastern part of Bali. Adjacent to Besakih Temple, in Pempatan Village, Rendang District, there is a temple called Pajinengan Gunung Tap Sai Temple. To increase and support the enthusiasm of the pamedek to the temple, it is necessary to improve facilities and infrastructure in the form of good road access, directions for the order of prayer, and public facilities such as toilets and washtafel for the pamedek. The method of data acquisition in this planning is by collecting data by interviewing the Pangempon Pura Pajinengan Gunung Tapsai and the observation method to see the original condition of the planning location so that the data is obtained is valid to facilitate planning for parking area arrangements and the layout of public facilities. Based on the results of interviews and observations at the location, the results obtained related to the inhibiting factors in this activity were the desire of the Pangempon to increase the area of ​​the temple, because the Pangempon wanted to maximize the provision of public facilities and arrangement of merchant stalls around the temple area. Based on the results of the previous discussion, it can be concluded that there is a need for structuring parking areas, public facilities, and merchant kiosks for which 2 (two) alternative plans are made. Alternative 1 is planned for 73 merchant kiosks measuring 4 x 5 meters, 124 four-wheel parking areas, 221 two-wheel parking areas, and 5 toilet units. Alternative 2 is planned for 47 merchant kiosks measuring 4 x 5 meters, 152 four-wheel parking areas, 287 two-wheel parking areas, and 5 toilet units